Potret Metode Sharḥ Hadis Isma’il Al-San’ani dalam Kitab Al-Tanwīr Sharḥ al-Jāmi‘ al-Ṣaghīr - Muhammad Alfreda Daib Insan Labib; Dadi Nurhaedi; Fajriyaturrohmah; Nurhadi; Zelvia Liska Afriani (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2025)
Al-Tanwīr Sharḥ al-Jāmi‘ al-Ṣaghīr book by Muhammad bin Isma’il Al-San’ani, is one of the important books of hadith syarah to be studied. The book, which is the Sharḥ al-Jāmi‘ al-Ṣaghīr by Al-Suyuthi, has a peculiarity compared to other similar books, like a Faiḍ Al-Qadīr Sharḥ al-Jāmi‘ al-Ṣaghīr by Syams al-Din Muhammad bin Zaid Ad-dīn, and Al-Istidrāk An-naẓīr ‘ala Al-Jāmi’ Al-Ṣaghīr by Syaikh Syihab Al-dīn Abi Al ‘Abbas Ahmad bin Muhammad al-matbūlī al-Syāfi’i. In this article, the problem studied is the method of syarah Al-San’ani through the analysis of the book of Al-Tanwīr. The problem is studied by descriptive analysis of analysis, namely by explaining important points in this book, then analyzing so as to produce conclusions in the form of methods in this book. The results of the study show that the book of Al-Tanwīr: (1) was conducted using the taḥlīlī method, that is, by expounding the matan hadith and giving syakl information to the matan hadith, then analyzing sentences, a few words, or even a word if that is possible to do sharḥ. (2) In modern academia, this method of writing books can be called descriptive-comparative-analysis. (3) The method of compiling this book is based on the order of the mu'jam letters (Alif, hamzah, ba, ta, tsa, and so on).